Cytotoxic Influence of Khat (Catha edulis (Vahl) Forssk. ex Endl) on Oral Fibroblasts, Squamous Carcinoma Cells, and Expression of α Smooth Muscle Actin - Azeem Ul Yaqin Syed; Muhammad A. Ahmed; Eman I. AlSagob; Mansour Al-Askar; Abdulrahman M. AlMubarak; Rizwan Jouhar; Abdul R. Ahmed; Sameer A. Mokeem; Nada Aldahiyan; Fahim Vohra; Tariq Abduljabbar (Applied Sciences, 2021)
The aim was to determine the cytotoxicity of Khat (Catha edulis (Vahl) Forssk. ex Endl) on normal oral fibroblasts (NOFs) and SCC4 (squamous carcinoma cells) along with expression of α-smooth muscle actin (α-SMA) in fibroblasts. Khat filtrate was prepared to obtain a concentrated viscous solution. NOFs and SCC4 cells were cultured in biological cabinets and were grown in Dulbeccos’ modified Eagles medium. Frozen cells were thawed at 37 °C and cell seeding was performed. NOFs and SCC4 cells were seeded on 96 well plates and allowed to attach. The medium was removed and a fresh medium containing different concentrations of Khat was added. The group without Khat served as a negative control and 4% paraformaldehyde as the positive control. Cell viability was assessed using the MTT assay and effect of Khat on fibroblast and SCC4 phenotypes was evaluated by immunostaining. Analysis of variance was used to assess data (p < 0.05). NOF 316 showed cell death in response to 4% paraformaldehyde, 12.5, 6.25, and 3.12 mg/mL of Khat. The highest concentration of Khat (25 mg/mL) failed to cause cytotoxicity of NOF 316. NOF 319 and NOF 26 displayed cell death at all concentrations of Khat, however, cytotoxicity was not dose dependent. NOF 18 and SCC4 cells showed dose-dependent cell death. NOF 316 showed α-SMA expression after 1 mg/mL of Khat exposure. Not all fibroblasts were α-SMA-positive, suggesting specific activation of a subset of fibroblasts. Khat is cytotoxic to NOF and SCC4 cells. Furthermore, it can also cause activation and phenotypic changes in oral fibroblasts, indicating a potential role in progression of oral squamous cell carcinoma.